Incidence and initial disease course of inflammatory bowel diseases in 2011 in Europe and Australia: results of the 2011 ECCO-EpiCom inception cohort - Vegh, Z; Burisch, J; Pedersen, N; Kaimakliotis, I; Duricova, D; Bortlik, M; Avnstrøm, S; Vinding, K Kofod; Olsen, J; Nielsen, K R; Katsanos, K H; Tsianos, E V; et al. (Journal of Crohn's & colitis, 2014)
BACKGROUND AND AIMS: The aim of the present study was to validate the IBD (inflammatory bowel diseases) incidence reported in the 2010 ECCO-EpiCom (European Crohn's and Colitis Organization-Epidemiological Committee) inception cohort by including a second independent inception cohort from participating centers in 2011 and an Australian center to investigate whether there is a difference in the incidence of IBD between Eastern and Western European countries and Australia. METHODS: Fourteen centers from 5 Eastern and 9 Western European countries and one center from Australia participated in the ECCO-EpiCom 2011 inception cohort. Patients' data regarding disease type, socio-demographic factors, extraintestinal manifestations and therapy were entered into the Web-based EpiCom database, www.ecco-epicom.eu. RESULTS: A total of 711 adult patients were diagnosed during the inclusion year 2011, 178 (25%) from Eastern, 461 (65%) from Western Europe and 72 (10%) from Australia; 259 (37%) patients were diagnosed with Crohn's disease, 380 (53%) with ulcerative colitis and 72 (10%) with IBD unclassified. The mean annual incidence rate for IBD was 11.3/100,000 in Eastern Europe, 14.0/100,000 in Western Europe and 30.3/100,000 in Australia. Significantly more patients were diagnosed with complicated disease at diagnosis in Eastern Europe compared to Western Europe (43% vs. 27%, p=0.02). CONCLUSION: Incidence rates, disease phenotype and initial treatment characteristics in the 2011 ECCO-EpiCom cohort were not significantly different from that reported in the 2010 cohort.
Keywords: kouření; Smoking; Anti-Inflammatory Agents, Non-Steroidal; Australia; kolonoskopie; lidé; mladiství; Adult; Crohn Disease; Immunosuppressive Agents; Middle Aged; mesalamin; Mesalamine; Inflammatory bowel diseases; stupeň závažnosti nemoci; Inception cohort; Female; Evropa; Austrálie; Incidence; Crohnova nemoc; Colitis, Ulcerative; Adolescent; Humans; Colonoscopy; stenóza; Steroids; antiflogistika nesteroidní; lidé středního věku; kohortové studie; Constriction, Pathologic; Cohort Studies; mužské pohlaví; mladý dospělý; steroidy; ženské pohlaví; imunosupresiva; Young Adult; Severity of Illness Index; Aged, 80 and over; senioři nad 80 let; Male; Aged; incidence; Europe; dospělí; ulcerózní kolitida; senioři